The self-perpetuation of the promise of care robots: how doubtful application scenarios become promising. (7th April 2023) - Schulz-Schaeffer, Ingo; Wiggert, Kevin; Meister, Martin; Clausnitzer, Tim
Abstract : This article employs a narrative approach to explain the self-perpetuation of the promise of care robots. For two decades, care robots have been viewed as a promising digital innovation that will relieve care workers from service tasks and thus improve the situation in the care sector. Though they still show a rather poor performance in real-world applications, the expectations are as high as ever. To explain the self-perpetuation of the promise of care robots, we investigate sensemaking practices in the discourse about care robots and show how a predominant overarching narrative as well as project-related sensemaking practices play out.